NEW DIRECTIONS IN PIDGIN AND CREOLE STUDIES - Baptista, Marlyse (Annual Review of Anthropology, 2005)
Abstract This chapter introduces the reader to the areas of previous investigation in creole studies, while outlining new directions the field is taking. The first section shows that, although the chief areas of interest have essentially remained the same for the past few decades, methodologies have changed toward a more comprehensive multilayered approach aimed at a better understanding of how individual creole languages emerge, evolve and function. The second section focuses particularly on cognitive processes involved in creole formation, such as restructuring, relexification, reanalysis, and dialectal leveling. In the third and last section, I critically evaluate the current state of affairs and point out potential obstacles and promising interdisciplinary trends.
Keywords: oral languages